بناء تاء الفاعل للمتكلم المفرد على الفتح عند إسناد الفعل الماضي إليه مجردًا من هاء المفعول في اللهجة السودانية: دراسة في ضوء علم اللغة الحديث. - أحمد عبد المجيد &#1581 (Dirasat: Human & Social Sciences, 2026)
Objectives: This research highlights the Sudanese dialect, responds to advocates of Sudaneseism, and records a linguistic phenomenon that is rare in Classical Arabic and its dialects but exists in Sudanese colloquial language—namely, the phenomenon of constructing the subject's Tā’ (the first-person singular pronoun Tā’) with fatḥah when attached to a past tense verb. This phenomenon has not been addressed by scholars before, as it has either vanished or evolved due to linguistic development over time. Methods: The research employs the inductive, descriptive, and analytical approach, utilizing Optimality Theory (OT) and the "harmonic evaluation table" to determine the level of optimality of the phenomenon both grammatically and in usage. Results: The study concluded that the phenomenon falls within a linguistically acceptable level according to modern linguistic analysis. It refutes the claim of Sudaneseism as an independent language and proposes logical and realistic solutions to address issues of identity and language in Sudan from an objective and neutral perspective, free from ethnic, sectarian, or racial biases. Conclusion: As unusual as this phenomenon may seem, it is linguistically acceptable from the perspective of modern linguistics. Furthermore, it is not exclusive to Sudan in a way that supports the notion of Sudaneseism, as it also extends to some regions in Africa and Salalah in Oman.